Sequencing of mitochondrial genomes of nine Aspergillus and Penicillium species identifies mobile introns and accessory genes as main sources of genome size variability - Joardar Vinita; Abrams Natalie F; Hostetler Jessica; Paukstelis Paul J; Pakala Suchitra; Pakala Suman B; Zafar Nikhat; Abolude Olukemi O; Payne Gary; Andrianopoulos Alex; Denning David W; Nierman William C (BMC Genomics, 2012)
Abstract Background The genera Aspergillus and Penicillium include some of the most beneficial as well as the most harmful fungal species such as the penicillin-producer Penicillium chrysogenum and the human pathogen Aspergillus fumigatus, respectively. Their mitochondrial genomic sequences may hold vital clues into the mechanisms of their evolution, population genetics, and biology, yet only a handful of these genomes have been fully sequenced and annotated. Results Here we report the complete sequence and annotation of the mitochondrial genomes of six Aspergillus and three Penicillium species: A. fumigatus, A. clavatus, A. oryzae, A. flavus, Neosartorya fischeri (A. fischerianus), A. terreus, P. chrysogenum, P. marneffei, and Talaromyces stipitatus (P. stipitatum). The accompanying comparative analysis of these and related publicly available mitochondrial genomes reveals wide variation in size (25–36 Kb) among these closely related fungi. The sources of genome expansion include group I introns and accessory genes encoding putative homing endonucleases, DNA and RNA polymerases (presumed to be of plasmid origin) and hypothetical proteins. The two smallest sequenced genomes (A. terreus and P. chrysogenum) do not contain introns in protein-coding genes, whereas the largest genome (T. stipitatus), contains a total of eleven introns. All of the sequenced genomes have a group I intron in the large ribosomal subunit RNA gene, suggesting that this intron is fixed in these species. Subsequent analysis of several A. fumigatus strains showed low intraspecies variation. This study also includes a phylogenetic analysis based on 14 concatenated core mitochondrial proteins. The phylogenetic tree has a different topology from published multilocus trees, highlighting the challenges still facing the Aspergillus systematics. Conclusions The study expands the genomic resources available to fungal biologists by providing mitochondrial genomes with consistent annotations for future genetic, evolutionary and population studies. Despite the conservation of the core genes, the mitochondrial genomes of Aspergillus and Penicillium species examined here exhibit significant amount of interspecies variation. Most of this variation can be attributed to accessory genes and mobile introns, presumably acquired by horizontal gene transfer of mitochondrial plasmids and intron homing.